ChemInform Abstract: Cu‐Catalyzed Arylation of the Amino Group in the Indazole Ring: Regioselective Synthesis of Pyrazolo‐Carbazoles. Issue 23 (June 2015) - Anil Kumar, K.; Kannaboina, Prakash; Dhaked, Devendra K.; Vishwakarma, Ram A.; Bharatam, Prasad V.; Das, Parthasarathi
Abstract 5‐ And 6‐aminoindazoles are arylated using various arylboronic acids and the products are cyclized to pyrazolocarbazoles.